GULA SEMUT AREN AS A LEADING AND POTENTIAL COMMODITIES OF SMALL AND MEDIUM MICRO BUSINESSES (UMKM) IN INDONESIAN INTERNATIONAL TRADE - Sutisna, Deden; Roeshartono; Haizam Bin Mohd Saudi, Mohd (International Journal of Psychosocial Rehabilitation, 2020)
Gula Semut Aren includes traditional products that are easily found on several islands or regions of Indonesia, from Aceh to West Papua. This product can be a potential Indonesian Small and Medium Micro Businesses (UMKM) commodity for the world market if it is managed wisely and professionally. The purpose of this study is to uncover the potential side of palm sugar as Indonesia’s leading small and medium microbusiness commodity in the fulfillment of world-class ant sugar products through export and import mechanisms in the next five years. Data analysis techniques used multiple linear regression with the following stages of research: 1) collecting data and information from the field and secondary data sources; 2) comparing data from research results and other sources of reference in accordance with the needs of the problem formulation; and 3) drawing conclusions from data trends to answer the scientific allegations from the research that was developed. The research results show that Indonesia in 2017 only contributed 3% to meet the world market of ant sugar. The remaining 97% was controlled by other countries such as 1) China, 2) the Netherlands, 3) the United States, 4) France, 5) Belgium, 6) Belgium, 7) Ireland, 8) Germany, 9) Korea Republic, 10) Indonesian, 11) Thailand, and 12) Other Country, while for the next 5 years, it will contribute 4.78% to meet the world market for this ant sugar. 95.22% controlled by other countries as above. Based on the results of the study, it can be concluded that Indonesian palm sugar has a huge potential for the world market in the future. This condition is supported by other factors such as: 1) The percentage of Indonesian market space for this product is 95.22%; 2) The area of Indonesia’s tropical land is wider than other countries that are overgrown with palm or kawung trees; 3) The human resources of palm or kawung farmers can still be developed; and 4) Institutions of small and medium microbusinesses as pivot developer farmers are still passionate about this sector.